Doping of Cu2ZnSnSe4 solar cells with Na+ or K+ alkali ions. Issue 6 (22nd January 2018) - Sahayaraj, Sylvester; Brammertz, Guy; Vermang, Bart; Mule, Aniket; Schnabel, Thomas; Meuris, Marc; Vleugels, Jef; Poortmans, Jef
Abstract : In this work, the addition of molar concentrations of Na + and/or K + in the form of fluorides during the processing of Cu2 ZnSnSe4 absorber layers was investigated. Abstract : In this work, the addition of molar concentrations of Na + and/or K + in the form of fluorides during the processing of Cu2 ZnSnSe4 absorber layers was investigated. The beneficial effect of alkali salts on the performance of CZTSe solar cells has been demonstrated through physical and electrical characterization. A maximum power conversion efficiency of 8.3% has been obtained through controlled addition of Na + and K + in the CZTSe absorber as opposed to 6.7% from uncontrolled addition of both. The open circuit voltage in both cases was very much the same but the devices with controlled addition showed lower p-type doping, a low density of charged defects and less band tailing compared to the rest.